An Intermediation-Based Model of Exchange Rates - Malamud, Semyon; Schrimpf, Andreas; Zhang, Yuan (Review of Financial Studies, 2025)
We develop a continuous-time general equilibrium model with intermediaries at the heart of international financial markets. Global intermediaries bargain with households and extract rents from providing access to foreign claims. By tilting state prices, intermediaries’ market power breaks monetary neutrality and makes international risk-sharing inefficient. Despite having zero net positions, markups charged by intermediaries significantly distort international asset prices, affecting exchange rate dynamics and their response to shocks. Our model can reproduce patterns consistent with several well-known exchange rate puzzles, such as deviations from uncovered and covered interest parity. All equilibrium quantities are derived in closed form, allowing us to pin down the underlying economic mechanisms explicitly.